2022
DOI: 10.1097/md.0000000000031622
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between placenta accreta scoring system, ultrasound staging, and clinical classification

Abstract: Placenta accreta spectrum (PAS) is a series of disorders, which means that the placental trophoblast invades into the myometrium of the uterine wall. It is a serious obstetric complication which could be detected by ultrasound prenatally. In order to compare our placenta accreta scoring system with prenatal ultrasound staging system and International Federation of Gynecology and Obstetrics (FIGO) clinical classification, we did a retrospective study including 105 patients diagnosed with PAS disorders by operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The ultrasonic beam can enter through the back of the bladder and the back of the lateral abdomen to prevent infection by reverberation artifacts and effectively present the lesions. [ 10 ] Zhao et al [ 16 ] showed that the rate of placenta previa, the rate of placenta vortex, the disappearance rate of posterior placental space, the thinning or disappearance rate of posterior placental muscle layer, and the rich rate of posterior placental BF in patients with PA were significantly higher than in those without PA. This shows that ultrasound examination can determine whether PA occurs in patients using relevant imaging features, which is consistent with the findings of this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ultrasonic beam can enter through the back of the bladder and the back of the lateral abdomen to prevent infection by reverberation artifacts and effectively present the lesions. [ 10 ] Zhao et al [ 16 ] showed that the rate of placenta previa, the rate of placenta vortex, the disappearance rate of posterior placental space, the thinning or disappearance rate of posterior placental muscle layer, and the rich rate of posterior placental BF in patients with PA were significantly higher than in those without PA. This shows that ultrasound examination can determine whether PA occurs in patients using relevant imaging features, which is consistent with the findings of this study.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Therefore, early accurate diagnosis of PA in scarred uteri is of great significance. Ultrasound is a commonly used diagnostic technique in obstetrics and gynecology, and has the advantages of strong repeatability, simple operation, low cost, and noninvasiveness, and can be used as the preferred examination method for PA. [10] However, examination results are easily affected by doctors' experience, examination time, placental attachment position, PA depth, etc. [10,11] Some studies have used a quantitative ultrasound scoring scale for prenatal diagnosis, which can more accurately distinguish the different degrees of implantation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study we included only patients with complete placenta previa defined as: placenta previa completely covering cervical OS. All patients with complete placenta previa was evaluated by Ultrasound Scoring System before operation, and ultrasound score ≥ 6 points was identified as suspicious placenta accreta spectrum (PAS) disorder as previous published article, [15][16][17] and patients with suspicious PAS disorder were excluded from the study. All patients in this study were well planned and prepared before operation, elective cesarean section was scheduled between 36 and 38 weeks according to Clinical Practice Guideline.…”
Section: Patientsmentioning
confidence: 99%